THIẾT LẬP QUY TRÌNH TỔNG HỢP IN VITRO PHÂN ĐOẠN RNA CỦA 5 LOÀI VIRUS EBOLA - Đinh, Thị Thu Hằng; Bùi, Tiến Sỹ; Hồ, Hữu Thọ; Nguyễn, Thái Sơn; Hoàng, Xuân Sử (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
DEVELOPMENT OF A NOVEL ASSAY FOR IN VITRO SYNTHESIS OF THE RNA FRAGMENTS SPECIFYING 5 EBOLA VIRUS SPECIES An in vitro transcribed RNA protocol of 5 pathogenic Ebola virus species ZEBOV, SEBOV, BEBOV, TEBOV, REBOV using synthesized plasmids was established with high efficient and following steps: (1) Cloning synthesized plasmids containing NP sequence and 3’UTR region of EBOV in E. coli; (2) 20 μl volume in vitro RNA transcription reaction: 5X TranscriptAid Reaction Buffer; 10 mM dNTPs mix; 0.8 - 1 μg plasmid DNA; 2 μl TranscriptAid Enzyme Mix and DEPC-treated water, 37 °C /2 hours, 2 μl DNase I, 37 °C /15 minutes by TranscriptAid T7 High Yield Transcription Kit. (3) Evaluation of in vitro transcribed RNA by electrophoresis and one-step RT-PCR assay. The in vitro transcribed RNA of 5 Ebola virus species with 900-1400 ng/µl concentration and from 1.8-2.1 A260/A280 ratio.